As inspirações estoicas da filosofia da natureza e do conhecimento de Margaret Cavendish - Matheus Tonani Marques Pereira (2021)
In this doctoral thesis, Margaret Cavendish’s texts concerning epistemology and natural philosophy are analysed in the light of a possible stoic inspiration. Cavendish is a 17th century thinker whose philosophy is, I argue, deeply indebted to the first stoics, more than what is usually recognized by the commentators. Firstly, in the part dedicated to the philosophy of knowledge, the study begins by presenting an interpretation on several stoic key concepts on the matter, with special attention being brought on the topic of perception and of the kataleptic impressions, both main contributions of the Greek stoa on knowledge. Furthermore, it is presented Cavendish’s philosophy of knowledge, in conjunction with some proposed proximities and distances from the stoic system. Following the comparison, which shows the stoic influence in Lady Margaret’s epistemology, it is proposed that this reading sheds some light in the famous cavendishian critique of the Royal Society’s experimentations with the newly invented optic instruments: the telescope and microscope. In the second unit, the physics portion of the philosophy of the porch is considered and Cavendish’s position is once again compared to it, considering both accounts describe the cosmos as a living, sensible and rational being. This part will discuss various topics on ontology, cosmology, and mechanics present in the physics of the Greek stoa and the philosophical texts of the duchess of Newcastle. The last part and chapter of the thesis is dedicated to the historical research on how the philosopheress could have been acquainted with the stoic philosophy of knowledge and of the world. The link between both theories is the lengthy History of Philosophy by Thomas Stanley, a work that Cavendish studied and that contained nearly every aspect of the thought of the first stoics that were later incorporated (or not) in her own philosophy. It is defended, in these pages, that Cavendish’s texts will show themselves clearer to us if we consider the possibility of a stoic inspiration in the original reflexions presented by the English philosopher. Another important goal of the text is to confront readings of Cavendish that assert that she would have only presented irrational fancies as her philosophy, which is absurd, if many of her main stances is also defended by one of the most influential antient school of thought. It is also defended that her intellectual system must be taken seriously by scholars because it possesses a considerable amount of internal coherence, contrary to those who want to see in Cavendish only the poor “Mad Madge”.